Analisis Kesulitan Pemahaman Konsep Siswa Dalam Menyelesaikan Soal Bangun Datar - Heha Syah Putri, Musfi’ah; Krisdianto Hadiprasetyo; Isna Farahsanti (Absis: Mathematics Education Journal, 2025)
Difficulty understanding concepts is the inability of students to understand something that has been known and remembered in a person's idea or idea based on their experience of an abstract object or event and using their own language. So that difficulties in understanding concepts can cause students to have difficulty understanding the next material or difficulty in solving problems. This study aims to describe the difficulties in understanding concepts experienced by students in solving flat building problems in grade VII A SMP Negeri 3 Jumantono for the 2023/2024 school year. This type of research is qualitative. The subjects in this study are students of grade VII A SMP Negeri 3 Jumantono for the 2023/2024 school year. The data collection technique uses tests and interviews. Testing the wetness of the data using the triangulation technique. Data analysis includes reduction, data presentation and conclusion drawn. The result of this study is that students of grade VII A SMP Negeri Jumantono experienced difficulties (1) restating a concept by 76.19%; (2) classifying objects according to certain properties (according to the concept) by 14.28%; (3) providing examples and non-examples of the concept by 85.71%; (4) presenting the concept in various forms of mathematical representation by 66.66%; (5) developing necessary or sufficient conditions for a concept by 100%; (6) applying concepts or problem-solving algorithms by 100%.